2018
DOI: 10.1093/icvts/ivy043
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine improves the outcomes in paediatric cardiac surgery: a meta-analysis of randomized controlled trials

Abstract: Perioperative administration of dexmedetomidine to paediatric patients undergoing cardiac surgery may shorten the duration of mechanical ventilation, LOS in the intensive care unit and in the hospital and reduce the incidence of junctional ectopic tachycardia. More high-quality randomized controlled trials are encouraged to verify the beneficial effect of dexmedetomidine before its clinical application in paediatric patients undergoing surgery for congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…A meta‐analysis performed by Liu et al 9 including nine trials with a total of 837 pediatric patients undergoing cardiac surgery revealed that the perioperative administration of dexmedetomidine shortened the MV duration in the ICU setting. In addition, dexmedetomidine reduced the risk of the incidence of JET in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A meta‐analysis performed by Liu et al 9 including nine trials with a total of 837 pediatric patients undergoing cardiac surgery revealed that the perioperative administration of dexmedetomidine shortened the MV duration in the ICU setting. In addition, dexmedetomidine reduced the risk of the incidence of JET in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Besides these effects, dexmedetomidine can decrease arrhythmias (atrial fibrillation), postoperative ventricular and supraventricular tachyarrhythmias. 8,9 Bradycardia is the most common cardiovascular side effect during the use of dexmedetomidine, which particularly occurs with the utilization of bolus doses. [7][8][9] For the last 3 years, we have used these two agents for FTE and UFTE after congenital cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study included 9 trials and 837 patients; DEX use was associated with shorter ICU-LOS, shorter ventilation time, and less JET. 19 Amula et al reviewed 322 infants having surgical repair of TOF or coarctation between 2013 and 2015. After implementation of an early extubation protocol, the likelihood of UFTE was nearly twice as likely if DEX was used.…”
mentioning
confidence: 99%